KEBERADAAN UMAT KRISTEN (KATOLIK) DI KECAMATAN KAYU ARO KABUPATEN KERINCI (1969-1980) - WIBOWO, ARE - (Pendidikan Sejarah, 2014)
This study discusses the about Christian religion (catholic) in sub kayu aro. inclusion of Christianity in sub Kayu Aro is inseparable from the efforts made by dutch Missionary or Missionary who came from java .Development of Christianity in Sub Kayu Aro is inseparable from the work of the pastor act done or people , such as activities in the economic, health, social, and education. The impact of the efents of the G 30 S/PKI in 1965 also contributed to the development of christian people in sub Kayu Aro. The Method in this study is the method of writing history is heuristic , source critic , interpretation historiography. The result research that christianity in Sub Kayu Aro is inseparable from the work done by Dutch missionaries and missionaries who came from java.